Les dynamiques de la PME : approches internationales - Saglio, Jean (Relations industrielles / Industrial Relations, 2002)
The article reviews the book, "Les dynamiques de la PME : approches internationales," edited by Bruno Courault and Philippe Trouvé.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Labor unions; SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z